Dealing with Food Allergies - Keith R. Schneider; Renée Goodrich Schneider; Soohyoun Ahn; Susie Richardson (EDIS, 2014)
A food allergy is an immune system reaction that happens after a person consumes what is normally considered a safe food. Food allergies occur more often in children than in adults: 4%–8% of those aged 4 or under and about 2% of adults are affected. Allergic reactions from food have led to over 20,000 emergency room visits per year. Annually, between 150 and 200 fatalities associated with food allergic reactions occur in the United States. This revised 4-page fact sheet was written by Keith R. Schneider, Renée Goodrich Schneider, Soohyoun Ahn, and Susie Richardson, and published by the UF Department of Food Science and Human Nutrition, January 2014.